Avaliação de vacinas recombinantes contra a leptospirose - Fagundes, Michel Quevedo (2012)
Leptospirosis is considered a global problem regarding both veterinary medicine and public health. In Brazil, the disease has greater impact in vulnerable populations, living in slums of great cities, where high morbidity and mortality occur. This situation requires the establishment of new intervention policies in order to reduce cases. Available vaccines to prevent the disease in humans and animals are notoriously underachieving, producing short term, serovar specific protection and collateral effects. New strategies are being employed to develop novel vaccines against leptospirosis, such as the characterization of recombinant proteins, construction of DNA vaccines, and use of alternative adjuvants. Surface exposed proteins LipL32, LigB, and LigA are highly conserved and found only in pathogenic serovars, therefore these were selected to be used in this study. LigA and LipL32 genes were cloned into the pVAX eukaryote expression vector to be used as DNA vaccines. rLigBNI and rLipL32 were assessed as subunit recombinant antigens using propolis as a co-adjuvant. Hamsters were immunized and the response was assessed through qPCR, ELISA, and lethal challenge. DNA vaccine containing the LipL32 gene, and the subunit rLigBNI vaccine had the highest results in the immune-stimulation assays. Furthermore, these imunogens were able to significantly protect animals against lethal challenge, demonstrating their potential for leptospirosis vaccine development.